Sa12b-Modified Functional Self-Assembling Peptide Hydrogel Enhances the Biological Activity of Nucleus Pulposus Mesenchymal Stem Cells by Inhibiting Acid-Sensing Ion Channels - Han, Letian; Wang, Ziyu; Chen, Haoyu; Li, Jie; Zhang, Shengquan; Zhang, Sumei; Shao, Shanzhong; Zhang, Yinshun; Shen, Cailiang; Tao, Hui (Frontiers in Cell and Developmental Biology, 2022)
Various hydrogels have been studied for nucleus pulposus regeneration. However, they failed to overcome the changes in the acidic environment during intervertebral disc degeneration. Therefore, a new functionalized peptide RAD/SA1 was designed by conjugating Sa12b, an inhibitor of acid-sensing ion channels, onto the C-terminus of RADA16-I. Then, the material characteristics and biocompatibility of RAD/SA1, and the bioactivities and mechanisms of degenerated human nucleus pulposus mesenchymal stem cells (hNPMSCs) were evaluated. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) confirmed that RAD/SA1 self-assembled into three-dimensional (3D) nanofiber hydrogel scaffolds under acidic conditions. Analysis of the hNPMSCs cultured in the 3D scaffolds revealed that both RADA16-I and RAD/SA1 exhibited reliable attachment and extremely low cytotoxicity, which were verified by SEM and cytotoxicity assays, respectively. The results also showed that RAD/SA1 increased the proliferation of hNPMSCs compared to that in culture plates and pure RADA16-I. Quantitative reverse transcription polymerase chain reaction, enzyme-linked immunosorbent assay, and western blotting demonstrated that the expression of collagen Ⅰ was downregulated, while collagen Ⅱ, aggrecan, and SOX-9 were upregulated. Furthermore, Ca2+ concentration measurement and western blotting showed that RAD/SA1 inhibited the expression of p-ERK through Ca2+-dependent p-ERK signaling pathways. Therefore, the functional self-assembling peptide nanofiber hydrogel designed with the short motif of Sa12b could be used as an excellent scaffold for nucleus pulposus tissue engineering. Moreover, RAD/SA1 exhibits great potential applications in the regeneration of mildly degenerated nucleus pulposus.